Che cos’è l’amore? Che cos’è la violenza? Cinque interviste a Massimo Fagioli - Fagioli, Massimo (Il sogno della farfalla, 2020)
This paper collects a number of interviews with the psychiatrist Massimo Fagioli edited by the journalists Ilaria Bonaccorsi and Elisa Liberatori Finocchiaro between 2010 and 2016. The psychiatrist, author of the Human Birth Theory, criticizes widespread ideas which have always affirmed original human violence and women’s innate inferiority. These ideas have largely contributed to confuse love with domination and abuse. Fagioli instead invites us to recognise the underlying mental illness concealed in episodes of violence against women and to consider a new idea of sexuality as a non conscious rapport between human beings which are at the same time different and equal.